Transforming Microfinance Institutions : Providing Full Financial Services to the Poor - Ledgerwood, Joanna; White, Victoria (Washington, DC: World Bank, 2012)
In response to a clear need by low-income people to gain access to the full range of financial services including savings, a growing number of microfinance NGOs are seeking guidelines to transform from credit-focused microfinance organizations to regulated deposit-taking financial intermediaries. In response to this trend, this book presents a practical "how-to" manual for microfinance institutions to develop the capacity to become licensed and regulated to mobilize deposits from the public. This book provides guidelines for regulators to license and regulate microfinance providers, and for transforming microfinance institutions to meet the demands of two major new stakeholders -regulators and shareholders. As such, it focuses on developing the capacity of NGO microfinance institutions to mobilize and intermediate voluntary savings. Drawing from worldwide experience, it outlines how to manage the transformation process and address major strategic and operational issues inherent in transformation including competitive positioning, business planning, accessing capital and shareholders, and how to "transform" the microfinance institutions human resources, financial management, management information systems, internal controls, and branch operations. Case studies then provide examples of developing a new regulatory tier for microfinance, and how a Ugandan NGO transformed to become a licensed financial intermediary.